First record of three Endophytic fungi isolated from xerophyte plants in Basra, Iraq - Lina K. Awad; Mohammed A. Fayyadh (Kufa Journal for Agricultural Sciences)
This study was conducted with the aim of isolating endophytic fungi from some xerophyte plants. In this study, three fungi were isolated from the internal tissues of some plants spread in the city of Basrah, Xenomyrothecium tongaense from the stem of Suaeda aegyptiace, Chaetomium megalocarpum from the roots, stem and leaves of Caroxylon jordanicola and Cephaliophora irregularis from the leaves of Cressa cretica. Fungus was identified based on its morphological features and molecular based on the amplification of the ITS gene region and the nucleolide sequence of the fungi was deposited in the genebank under accession number NR-154511.1, KT371335.1 and OM245865.1 for fungi Xenomyrothecium tongaense, Chaetomium megalocarpum and Cephaliophora irregularis, respectively. This is the first study in which these fungi are isolated from desert in Iraq.